Early Resuscitation in Paediatric Sepsis Using Inotropes – A Randomised Controlled Pilot Study in the Emergency Department (RESPOND ED): Study Protocol and Analysis Plan - Harley, Amanda; George, Shane; King, Megan; Phillips, Natalie; Keijzers, Gerben; Long, Debbie; Gibbons, Kristen; Bellomo, Rinaldo; Schlapbach, Luregn J. (Frontiers in Pediatrics, 2021)
Introduction: Septic shock in children still carries substantial mortality and morbidity. While resuscitation with 40-60 mL/kg intravenous fluid boluses remains a cornerstone of initial resuscitation, an increasing body of evidence indicates potential for harm related to high volume fluid administration. We hypothesize that a protocol on early use of inotropes in children with septic shock is feasible and will lead to less fluid bolus use compared to standard fluid resuscitation. Here, we describe the protocol of the Early Resuscitation in Paediatric Sepsis Using Inotropes – A Pilot Randomised Controlled Pilot Study in the Emergency Department (RESPOND ED). Methods and analysis: The RESPOND ED study is an open label randomised controlled, two arm, multicentre pilot study conducted at four specialised paediatric Emergency Departments. Forty children aged between 28 days and 18 years treated for presumed septic shock will be randomized in a 1:1 ratio of early inotropes versus standard fluid resuscitation. Early inotrope treatment is defined as the commencement of a continuous intravenous adrenaline infusion after 20 mL/kg fluid bolus resuscitation. Standard fluid resuscitation is defined as delivery of 40 to 60 mL/kg fluid bolus resuscitation prior to commencement of inotropes. In addition to feasibility outcomes, survival free of organ dysfunction censored at 28 days will be assessed as the main clinical outcome. The study cohort will be followed up at 28 days, and at six months post enrolment to assess quality of life and functional status. Biobanking nested in the study cohort will be performed to enable ancillary biomarker studies. Ethics and dissemination: The trial has ethical clearance (Children’s Health Queensland, Brisbane, HREC/18/QCHQ/49168) and is registered in the Australian New Zealand Clinical Trials Registry (ACTRN12619000828123). Enrolment commenced on July 21st, 2019. The primary manuscript will be submitted for publication in a peer-reviewed journal. Trial registration number: ACTRN12619000828123